Immediate treatment effects of high-dose methotrexate and cranial irradiation on neuropsychological functions of children treated for acute lymphoblastic leukemia at a regional cancer center - Chidambaram, Sundaramoorthy; Seshachalam, Arun; Elangovan, Vidhubala; Rajendranath, Rejiv (Indian Journal of Medical and Paediatric Oncology, 2014)
Context: Overall cure rates for pediatric acute lymphoblastic leukemia (ALL) have improved; however, the neuropsychological sequelae of ALL treatment have not been adequately documented in India. Aims: The present study assesses the immediate effects of ALL treatment on neuropsychological functioning, at the Regional Cancer Center in Chennai, South India. Materials and Methods: Newly diagnosed with ALL patients (n = 24) (aged 6-15 years; 13M:11F) registered between March 2008 and February 2009 were included. Patients who had received high-dose methotrexate (HD-MTX) and cranial radiotherapy (CRT) as part of their treatment were enrolled for the study. Neurocognitive assessments were done to assess various functions such as performance intelligence, visuo-perception, visuo-spatial, perceptual organization, processing speed, planning, working memory, and immediate verbal memory (IVM) (Malin′s intelligence scale); verbal fluency (ideation fluency test) and verbal attention (vigilance test). Three assessments were done during induction (baseline), after re-induction phase (second) and during the maintenance phase (third). Results: The patients performed significantly worse in the third assessment (mean duration from diagnosis 17.48 months) on performance intelligence quotient (PIQ), visuo-perception, visuo-spatial, processing speed, planning, IVM, verbal attention, and verbal fluency (P < 0.05), there were no significant changes observed in visuo-perceptual organization and working memory (P > 0.05). Significant difference was observed between age groups 6 and 10 (41.7%) and 11-15 years (58.3%) in perceptual organization, verbal fluency, and verbal attention (P < 0.05) and no gender difference was observed across the three assessments (P > 0.05). Conclusions: Combining HD MTX and CRT had an immediate effect on neuropsychological sequelae among the children with ALL, however, long-term evaluation is recommended to study the long-term effects.
Keywords: Acute lymphoblastic leukemia; central nervous system prophylaxis; chemotherapy; cranial radiation; neuro-cognitive functions